Age-related changes in the effects of strength training on lower leg muscles in healthy individuals measured using MRI. Issue 1 (20th July 2017) - Psatha, Maria; Wu, Zhiqing; Gammie, Fiona; Ratkevicius, Aivaras; Wackerhage, Henning; Redpath, Thomas W; Gilbert, Fiona J; Meakin, Judith R; Aspden, Richard M
Abstract : Background: We previously measured the rate of regaining muscle strength during rehabilitation of lower leg muscles in patients following lower leg casting. Our primary aim in this study was to measure the rate of gain of strength in healthy individuals undergoing a similar training regime. Our secondary aim was to test the ability of MRI to provide a biomarker for muscle function. Methods: Men and women were recruited in three age groups: 20–30, 50–65 and over 70 years. Their response to resistance training of the right lower leg twice a week for 8 weeks was monitored using a dynamometer and MRI of tibialis anterior, soleus and gastrocnemius muscles at 2 weekly intervals to measure muscle size (anatomical cross-sectional area ( ACSA )) and quality ( T2 relaxation). Forty-four volunteers completed the study. Results: Baseline strength declined with age. Training had no effect in middle-aged females or in elderly men in dorsiflexion. Other groups significantly increased both plantarflexion and dorsiflexion strength at rates up to 5.5 N m week -1 in young females in plantarflexion and 1.25 N m week -1 in young males in dorsiflexion. No changes were observed in ACSA or T2 in any age group in any muscle. Conclusion: Exercise training improves muscle strength in males at all ages except the elderly in dorsiflexion. Responses in females were less clear with variation across age and muscle groups. These results were not reflected in simple MRI measures that do not, therefore, provide a good biomarker for muscle atrophy or the efficacy of rehabilitation.